Answer:
see explanation
Explanation:
(6)
multiply each term inside the parenthesis by the fraction outside
= (
× k ) + (
× - 4)
=
k + (- 2) =
k - 2
(7)
A reminder that the absolute value function always returns a positive value.
The value inside the bars can be positive or negative but the result is always positive.
2 + |- 5 + 4 | = 2 + |- 1 | = 2 + 1 = 3
(8)
A |- 4 - 5 | = | - 9 | = 9
B - | 9 | = - 9 ← does not equal 9
C | - 9 | = 9
D | 9 | = 9
(9)
given 3(2n + 1) + 4(n - 2)
distribute both parenthesis and collect like terms
= 6n + 3 + 4n - 8
= (6n + 4n) + (3 - 8)
= 10n + (- 5) = 10n - 5